Some Fixed Point Results for Hybrid Contraction in Metric Spaces and Ulam-Hyers Stability (European Journal of Pure and Applied Mathematics, 2025)
In the present manuscript, we introduce a new notion of (β, ϕ)− admissible hybrid contractions in metric spaces and establish fixed point results in the setting of these spaces. The derived results extend the reported findings of the past. The derived result is supplemented with a non-trivial example. We have also analyzed the Ulam-Hyers stability and well-poisedness as anapplication to the derived results.
Keywords: (β, ϕ)−admissible hybrid contraction; fixed point; Ulam - Hyers stability; metric space